P–160 Sibling oocytes cultured in a time-lapse versus benchtop incubator: limited exposure of embryos outside the incubator improves outcomes. (6th August 2021) - Munck, N D; Nobrega, N; Abdala, A; El-Damen, A; Arnanz, A; Bayram, A; Elkhatib, I; Lawrenz, B; Fatemi, H M
Abstract: Study question: Does the limited exposure of embryos outside the incubator, during evaluation and changeover, have an impact on the blastocyst development, blastocyst quality and euploid outcomes? Summary answer: Exposure of embryos outside the incubator, negatively impacts the number, quality and euploidy rate of day 5 blastocysts. What is known already: The laboratory environment with its culture conditions is one of the crucial elements of the delicate equation to a successful ART outcome. It has been shown that increased fluctuations in the culture conditions have a considerable impact on the number of blastocysts obtained and cycle outcomes. Compared to conventional benchtop incubators, Time Lapse Technology (TLT) incubators capture images of the embryo and allow morphologic and morphokinetic assessment without disturbance during incubation. Several studies have been published comparing the efficiency, safety and outcome performance between conventional and TLT incubators, however, none of them explored the euploid outcomes. Study design, size, duration: An observational sibling oocyte study was performed at ART Fertility Clinics, Abu Dhabi between March 2018 and April 2020 and included data of 796 mature oocytes injected from 42 stimulation cycles. Sibling oocytes were randomly split between 2 different incubators: 12 oocytes were assigned to the twelve wells of the EmbryoscopeTM (ES) and the remaining oocytes were cultured in a conventional benchtop incubator, G185 K-System (KS). Participants/materials, setting, methods: Embryos from patients with primary or secondary infertility, who underwent ovarian stimulation for ICSI and PGT-A through NGS on trophectoderm biopsies, were eligible. All patients had at least 16 fresh mature oocytes, randomly allocated to two different incubators after ICSI: 503 (63.2%) oocytes were cultured in ES and 293 (36.8%) in KS. The fertilization, cleavage, useable blastocyst and euploid rates, as well as embryo/blastocyst qualities were assessed to evaluate each incubator's performance. Main results and the role of chance: The fertilization and cleavage rates were similar between incubators. Total useable blastocyst rate (64.8% vs 49.6%, p < 0.001) was significantly higher for embryos cultured in ES, mainly due a higher percentage of blastocysts biopsied on day 5 in ES (67.8% vs 57.0%, p = 0.037), with improved quality (p = 0.008). There was no difference in the total euploid rate between ES and KS (59.9% vs 50.4%, p = 0.314), but a significantly higher euploid rate was seen for blastocysts cultured in ES and biopsied on day 5 (63.5% vs 37.4%, p = 0.001). Day 3 embryo quality and total biopsied blastocyst quality was not different between incubators. No difference was observed in the total useable blastocyst development from good (p = 0.0832) and poor (p = 0.112) quality day 3 cleavage stage embryos. However, when stratifying according to the day of blastocyst development, poor quality embryos on day 3 showed superior blastocyst formation on day 5 when cultured in ES (64.1% vs 39.1% for day 5 and 35.9% vs 60.9% for day 6, p = 0.005). Accordingly, blastocyst formation from poor quality embryos on day 3, was shifted to day 6 for embryos cultured in KS. This difference in the day of blastocyst development was not observed for good quality cleavage stage embryos (p = 0.917). Limitations, reasons for caution: The current observational study needs confirmation in a prospective trial and should also include the implantation potential of the euploid blastocysts, which was not followed in the current study. A good prognosis population (≥16 mature oocytes) was studied and may not reflect the outcomes in patients with lower oocyte numbers. Wider implications of the findings: This work builds evidence to the solid introduction of the TLT incubators to the clinical routine, as the reduced exposure of embryos outside the incubator – and hence decreased stress - improves the blastocyst development. Trial registration number: NA